UNCOVERING DIVERSIFICATION BENEFITS: RETURN SPILLOVERS IN USA ESG AND NON-ESG ORIENTED BANKS - Zafar, Madiha; Qarni, Muhammad Owais (PEOPLE: International Journal of Social Sciences, 2024)
Financial products are interconnected through the balance sheet and affect the overall economic system by connectedness. Investors are interested in the connectedness of markets, so our study investigated spillover dynamics and their influence on ESG and non-ESG-oriented banks in the USA. Our dataset comprises 2319 observations from January 1, 2015, to November 22, 2023. We employed the spillover index of Diebold and Yilmaz (2012) to conduct an extensive analysis of ESG-oriented and non-ESG-oriented banks in the USA. The study uncovered significant differences in interconnectedness and spillover effects between ESG-oriented and non-ESG-oriented banks, particularly during regular periods and the COVID-19 pandemic. ESG-oriented banks, in particular, exhibit higher levels of interconnectedness, with notable spillovers among themselves, indicating a need for cross-market diversification to manage risk. In contrast, non-ESG-oriented banks demonstrate lower interconnectedness and spillover effects. The study highlights the potential benefits of portfolio diversification across ESG and non-ESG banks. The research concludes that such diversification can offer significant risk reduction benefits. Findings suggested that banks must incorporate ESG and non-ESG investments in their portfolio to mitigate overall risk. Banks’ adoption of ESG standards may lead to investing in fewer projects, leading to ESG constraints in portfolio optimization. In this way, ESG investment restricts and constrains the diversification of portfolios, which increases risk and contagion.